CNTs threaded (001) exposed TiO2 with high activity in photocatalytic NO oxidation. Issue 5 (18th January 2016) - Xiao, Shuning; Zhu, Wei; Liu, Peijue; Liu, Fanfan; Dai, Wenrui; Zhang, Dieqing; Chen, Wei; Li, Hexing
Abstract : CNTs-threaded (001) exposed TiO2 provides a high percentage of active facets and direct electron highway to largely enhance solar NO oxidation. Abstract : A microwave-ionothermal strategy was developed for in situ synthesis of CNTs threaded TiO2 single crystal with a tunable percentage of surface exposed (001) active facets. The CNTs were used as microwave antennas to create local "super hot" dots to induce Ti 3+ adsorption and hydrolysis, thereby leading to a good assembly of (001) facets exposed single crystalline TiO2 threaded by the CNTs in the presence of Hmim[BF4 ] ionic liquid. Due to the high percentage of the active (001) facets of single crystal TiO2 and the direct electron transfer property of the CNTs, the as-prepared CNTs–TiO2 composite showed a photocatalytic NO removal ratio of up to 76.8% under UV irradiation. In addition, with self-doped Ti 3+, the CNTs–TiO2 composite also exhibited an enhanced activity under irradiation with either solar lights or visible lights, showing good potential in practical applications for environmental remediation.